The The Influence of Digital Identity on Indonesia's Young Generation on Awkarin's Instagram Post: Pengaruh Identitas Digital terhadap Generasi Muda Indonesia pada Postingan Instagram Awkarin - Perlita, Lora Langit Rafidah Azaria; Munawaroh, Madinatul (Procedia of Social Sciences and Humanities, 2025)
Awkarin's digital identity has become an interesting phenomenon among the young generation of Indonesia. This article explores how Awkarin builds and maintains his online identity across various social media platforms, as well as its impact on the behavior and views of the younger generation. Through a combination of authentic, controversial, and inspiring content, Awkarin managed to manage diverse audiences while facing the challenge of 'context collapse', where various audience segments meet in one digital space. In addition, this article also highlights the strategies that Awkarin uses to maintain its authenticity amid the risks and opportunities that come with privacy and surveillance in the digital environment. With this in-depth analysis, it is hoped that it can provide valuable insights for the younger generation on the importance of building a strong and authentic digital identity, as well as how to navigate the online world wisely and carefully.